Cardanol‐Based and Formaldehyde‐Free Flexible Phenolic Networks. Issue 7 (6th June 2018) - Briou, Benoit; Caillol, Sylvain; Robin, Jean‐Jacques; Lapinte, Vincent
Abstract : Commercial novolac‐type phenolic thermosets are mainly synthesized from highly toxic precursors such as phenol and formaldehyde. Herein, the phenolic chemistry is renewed with bio‐based and non‐toxic precursors such as cardanol and nonanal to elaborate flexible phenolic thermosets. The two‐step novolac strategy involves the synthesis of a cardanol nonanal pre‐polymer (PCN) prior to its cross‐linking in presence of a supplementary amount of nonanal hardener. The curing process is optimized by rheology measurement and thermogravimetry analysis. The alkyl chains of this phenolic network induces soft mechanical properties acting as internal plasticizers. The softening of the resulting networks do not induce a loss of thermal stability. Showing a good compromise between softness and high thermal resistance, cardanol‐nonanal networks (RCN) seem to be relevant examples of an innovative and biobased approach for phenolic chemistry to design bio‐sourced materials without any petro‐based or hazardous molecules. Practical Applications : Various practical applications where smooth and soft coatings are employed can be considered. Novolac chemistry for bio‐based and notoxic resources : cardanol and nonanal. Softness and high thermal resistance phenolic resins are elaborated. These materials are based on internal plasticized cross‐linked materials. Abstract : Novolac chemistry for bio‐based and notoxic resources : cardanol and nonanal. Softness and high thermal resistance phenolic resins are elaborated. These materials are based on internal plasticized cross‐linked materials.